Assessment of Impact of Economic Sustainability on Shareholder Return and Economic Profit of BRICS Industrial Companies Following Digital Transformation Strategy - Sergei Grishunin; Ekaterina Burova; Svetlana Suloeva (International Journal of Technology, 2023)
We investigated the impact of Economic Sustainability (ES) practices of digitally oriented industrial companies in BRICS (Brazil, Russia, India, China, and South Africa) in various horizons. The relevance is underpinned by numerous controversies in the literature on the topic. The sample included 257 industrial companies from BRICS in 2017-2021. Economic profit in the long-term and short-term was measured by Total Shareholder Return (TSR) and Economic Value Added (EVA), respectively. We found that the improvements in resource use, enhancements in the workforce and responsible product development had a positive and significant influence on the TSR of BRICS companies. Conversely, we discovered the negative impact of social practices on companies’ EVA. Firms from Brazil and India with stronger ESG practices provided higher returns for shareholders, while there was a significant and negative linkage between ES and EVA for Chinese firms. Cross-industry analysis showed that ESG practices had an additional positive and significant impact on the TSR of firms in the basic materials and technology sectors. However, there was an additional negative and significant impact of ES practices on EVA in consumer cyclical and energy sectors. The novelty is driven by (1) exploring the impact of ESG practices on companies’ value at BRICS; (2) considering previously overlooked metrics of TSR and EVA; and (3) applying granular ES metrics instead of aggregated ones.